Use of passive structures in ESL narrative compositions among Malay students - Junisah, M.F.K.; Kulwindr Kaur, G.S. (2016)
Narrative compositions provide essential information regarding the narrators'" linguistic competence. This study was conducted to explore the use of passive 'structures in ESL narrative compositions; specifically, to describe the passive voice structured by the Malay students of SMK Tanjung Datuk in their ESL narrative . compositions, and to describe the effect of their mother tongue (the Malay language) in structuring the passive sentences in English. The study combined both quantitative and qualitative methods, using the Lexical Functional Grammar (LFG) by" loan Bresnan (1970) as the theoretical framework. LFG was chosen as the framework of the study as it involves both constituent structure and functional structure in sentence analysis. Therefore, a better illustration and explanation on the function-dependent rules like passivisation across languages are better portrayed. The sample for this study involved only 30 Form 4 Malay students (the participants) of intermediate level of proficiency, from SMK Tanjung Datuk, Pengerang, Johor, The participants were given a question on a narrative composition taken from the real 2014 1119SPM English Paper to be answered within one hour. Two interview sessions with three participants and the two inter-raters for this study were also conducted in order to support and clarify the data gathered. The findings showed that the structures of the passive voice in the ESL narrative compositions of "the. participants comprised adjectival, resultative and verbal passives. The participants were able to utilize the passive voice in their ESL narrative compositions, but the structures written were mostly inaccurate due to the influence of their mother tongue (the Malay language) in constructing the passives in the English language, whereby a negative transfer occurred from LIto L2 in terms "ofthe sentence types, sentence patterns and the formation of the pass.ive verbs."